Comparison of fish detections, community diversity, and relative abundance using environmental DNA metabarcoding and traditional gears. Issue 4 (9th October 2019) - Sard, Nicholas M.; Herbst, Seth J.; Nathan, Lucas; Uhrig, Genelle; Kanefsky, Jeannette; Robinson, John D.; Scribner, Kim T.
Abstract: Background: Detecting species at low abundance, including aquatic invasive species (AIS), is critical for making informed management decisions. Environmental DNA (eDNA) methods have become a powerful tool for rare or cryptic species detection; however, many eDNA assays offer limited utility for community‐level analyses due to their use of species‐specific (presence/absence) 'barcodes'. Metabarcoding methods provide information on entire communities based on sequencing of all taxon‐specific barcodes within an eDNA sample. Aims: Evaluate measures of fish species detections, community diversity, and estimates of relative abundance based on eDNA metabarcoding and traditional fisheries sampling approaches in the context of fish community characterization and AIS survellience. Materials and Methods: In 2016, eight limnologically diverse lakes (surface area range: 13 – 1, 728 ha) in Michigan, USA were sampled using a variety of traditional fisheries gears to characterize fish community composition. Environmental DNAs from surface (33 ± 6, mean ± 1 SD) and benthic (14 ± 2) water samples from each lake were isolated and amplified for two metabarcoding markers (mitochondrial 12S and 16S rDNA loci) using fish‐specific primers. Fish species detected within each lake were determined by comparing the sequencing data to a database of sequences from native Michigan fish species and 19 AIS on the Michigan's Watch List. Results: Analysis of species accumulation curves indicated multi‐locus eDNA metabarcoding assays can enhance species detection capacities and characterize 95% of a fish community in fewer sampling efforts than traditional gear (range: 2 – 62, median: 14). In addition, all AIS detected in traditional gear samples were also detected by eDNA, while some AIS detected by eDNA assays were absent from traditional gear samples. Discussion: Results reported here are, in part, driven by the lack of species‐selectivity during eDNA sampling events. Given the efficacy of eDNA assays, we suggest multi‐locus eDNA metabarcoding assays be implemented in early detection efforts. Abstract : The early detection of aquatic invasive species (AIS) is critical for a range of conservation issues. Environmental DNA (eDNA) metabarcoding methods (dark grey) were compared to traditional fisheries gears (light grey) to evaluate how each characterized a fish community. Results suggest that fish communities, including low abundance AIS, could be characterized more fully and in fewer samples with a multi‐locus eDNA metabarcoding assay.